Opportunities to improve water productivity in farmer-led irrigation: a case study of Ethiopia - Tegegne, Desalegn (Springer, 2025)
To construct economic growth and poverty reduction, farmer-led irrigation is increasing nowadays in many African, South Asian, and Latin American countries. Smallholder farmers’ vulnerability to climate shocks due to rainfall variability, frequent droughts, and inadequate water resources, which threaten agricultural productivity and food security is known. Understanding the current and future crop water demand is key for improving agricultural productivity, and bringing food security, especially in arid and semi-arid areas where irrigation is needed to overwhelm shortage and rainfall variability. Water productivity (WP) is to produce more yield with less water use, increase income, improve livelihoods, and bring ecological benefits at less social and environmental costs per unit of water used. Some of the approaches for increasing WP include more yield with proper water use, changing the cropping pattern from low to high-value crops, decreasing costs related to social, health, and environmental aspects, and achieving more livelihood support such as more job opportunities, diversified nutritious food, and income for the same amount of water. Potential opportunities are vastly needed to achieve the productivity of irrigated agricultural systems around the globe through the full engagement of smallholder farmers, public-private sectors, government entities, and potential water resource management stakeholders. This chapter will briefly discuss opportunities for improving WP about farmer-led irrigation, focussing on smart utilization of water resources and agronomic practices to achieve higher yields using less water. Using the available water sources and low-cost water-lifting alternative technology options, implementing efficient irrigation water application methods, practicing deficit and supplemental irrigation techniques, and adopting climate-smart on-farm water management techniques and technologies are potential opportunities for improving WP in farmer-led irrigation areas.